2008
DOI: 10.4049/jimmunol.180.1.609
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-γ Ligand, 15-Deoxy-Δ12,14-Prostaglandin J2, Reduces Neutrophil Migration via a Nitric Oxide Pathway

Abstract: Ligands for peroxisome proliferator-activated receptor γ (PPAR-γ), such as 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) have been implicated as a new class of anti-inflammatory compounds with possible clinical applications. Based on this concept, this investigation was designed to determine the effect of 15d-PGJ2-mediated activation of PPAR-γ ligand on neutrophil migration after an inflammatory stimulus and clarify the underlying molecular mechanisms using a mouse model of peritonitis. Our results demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 55 publications
4
57
1
Order By: Relevance
“…Such association may limit binding of the leukocyte to the proadhesive ICAM-1. We have previously demonstrated that 15d-PGJ 2 was able to inhibit ICAM-1 (12). In addition, according to the current study, the use of 15d-PGJ 2 -NC at doses of 3 and 10 mg/kg increased the expression of the CD55 molecule in the gingival tissue.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Such association may limit binding of the leukocyte to the proadhesive ICAM-1. We have previously demonstrated that 15d-PGJ 2 was able to inhibit ICAM-1 (12). In addition, according to the current study, the use of 15d-PGJ 2 -NC at doses of 3 and 10 mg/kg increased the expression of the CD55 molecule in the gingival tissue.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, our and other research groups have demonstrated the anti-inflammatory activity of exogenously administered 15d-PGJ 2 (12)(13)(14)(15)(16)(17)(18). However, it has been estimated that .50% of the 15d-PGJ 2 added exogenously to a biological system binds to albumin (11).…”
Section: {‖mentioning
confidence: 99%
“…This dose of 15d-PGJ 2 was chosen based on a previous study showing that it was effective as an anti-inflammatory agent (Napimoga et al 2008). The control group of infected animals (n = 8) was treated with DMSO only.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the release of TNF-α, IFN-γ, IL-4 and IL-10 by Con-A-stimulated splenocytes obtained from infected mice was significantly inhibited by treatment of the animals with salicylate or meloxicam (Michelin et al 2005). Interestingly, indomethacin binds and activates the peroxisome proliferator-activated receptor γ (PPARγ), a ligandactivated transcription factor known to play a pivotal role in adipogenesis (Lehmann et al 1997) in addition to the inflammatory process (Di Paola & Cuzzocrea 2007, Napimoga et al 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation